2017
DOI: 10.1590/1806-9282.63.04.307
|View full text |Cite
|
Sign up to set email alerts
|

Alternative option for osteogenesis imperfecta and trigeminal neuralgia

Abstract: Osteogenesis imperfecta (OI) is a bone disorder that can lead to skull base deformities such as basilar invagination, which can cause compression of cranial nerves, including the trigeminal nerve. Trigeminal neuralgia in such cases remains a challenge, given distorted anatomy and deformities. We present an alternative option, consisting in cannulation of the foramen ovale and classical percutaneous treatment. Percutaneous balloon microcompression was performed in a 28 year--old woman with OI and severe trigemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…3.12 | Other clinical manifestations: Presence of basilar invagination, gastrointestinal issues, and genitourinary problems A paucity of research has been observed in the literature concerning basilar invagination, gastrointestinal issues, and genitourinary problems. Briefly, three case reports addressed the issue of trigeminal neuralgia, which was due to basilar invagination (Hajioff, Dorward, Wadley, Crockard, & Palmer, 2000;Iwai, Ishibashi & Yamanaka, 2018;Ruschel, Agnoletto, Hunhevicz, Almeida, & Arruda, 2017). Augustin, Jelincic, Majerovic, and Stefancic (2007) examined the obstructed colon of a woman with OI Type III caused by a pelvic stenosis.…”
Section: Vision Impairment: Thin Central Corneal Thickness and Riskmentioning
confidence: 99%
“…3.12 | Other clinical manifestations: Presence of basilar invagination, gastrointestinal issues, and genitourinary problems A paucity of research has been observed in the literature concerning basilar invagination, gastrointestinal issues, and genitourinary problems. Briefly, three case reports addressed the issue of trigeminal neuralgia, which was due to basilar invagination (Hajioff, Dorward, Wadley, Crockard, & Palmer, 2000;Iwai, Ishibashi & Yamanaka, 2018;Ruschel, Agnoletto, Hunhevicz, Almeida, & Arruda, 2017). Augustin, Jelincic, Majerovic, and Stefancic (2007) examined the obstructed colon of a woman with OI Type III caused by a pelvic stenosis.…”
Section: Vision Impairment: Thin Central Corneal Thickness and Riskmentioning
confidence: 99%
“…Osteogenesis imperfecta (OI) is known to be a disease characterized by bone fragility triggered by a qualitative or quantitative defect of collagen type one synthesized by osteoblasts. 1 The frequency of 6-7 / 100,000 individuals has been shown in studies, and in Brazil it is estimated that there are around 12,000 individuals with this diagnosis. 2 OI is defined as a rare genetic disease that primarily affects tissue rich in collagen type one present in bone tissue, ligaments, tendons, dentin, sclera and skin.…”
mentioning
confidence: 97%
“…6 It is understood that OI, as a rare disease, does not have wide wisdom and management by health professionals, however, individuals affected by such pathology need specialized assistance for their clinical condition. 1,4 For the definition of the research scenario, a survey was conducted from the institute's databases and it was found that 164 children were hospitalized from 2009 to 2019 with diagnosis of OI in order to undergo some surgical treatment due to injuries caused by the underlying pathology. Among the children who underwent hospitalization and surgery, 7.4% were infants, 27% were preschoolers, 45% were school age and 20.6% were adolescents.…”
mentioning
confidence: 99%
See 2 more Smart Citations